Hubungan Konsep Diri dengan Penyesuaian Diri Siswa SMP di Sekolah - Marpaung, Vika Wijaya; Zikra, Zikra (ALSYS, 2025)
This research is motivated by the existence of students who have problems with adjustment, where students have not been able to adjust, violate school regulations, have difficulty adapting to new environments, often play truant, do not comply with dress codes, are not active in participating in lessons and school activities, are alone at school, There are students who still don't know the name of the teacher who teaches in the class and don't know a place in the school environment. The objectives of this research are: : (1) describe the self-concept of students at SMPN 1 Lembah Gumanti; (2) describe the students' adjustment at SMPN 1 Lembah Gumanti; (3) examine the relationship between self-concept and self-adjustment of students at SMPN 1 Lembah Gumanti. This research uses quantitative methods with descriptive correlational research. The sample in this study was 130 class VII students at SMPN 1 Lembah Gumanti. The sampling technique was simple random sampling technique. The instruments used in this research are self-concept instruments and self-adjustment instruments with a Likert scale model. The data analysis techniques used are descriptive analysis, analysis requirements testing, and Pearson product moment correlation test with the help of SPSS version 20. The results of the research show that: (1) students' self-concept is generally in the medium category with a percentage of 52.31%, which means many students in the sample had a moderate self-concept; (2) students' self-adjustment is generally in the medium category with a percentage of 39.23%, which means that many students in the sample have moderate self-adjustment; (3) there is a significant positive relationship between self-concept and self-adjustment of students at SMPN 1 Lembah Gumanti with a correlation coefficient of 0.701 at a significance level of 0.000. This means that the higher the self-concept, the higher the student's self-adjustment and vice versa. Based on the research results that have been obtained, it is hoped that guidance and counseling teachers can play an active role in efforts to improve the self-concept and self-adjustment of junior high school students by providing assistance in the form of services related to self-concept and self-adjustment. The services that can be provided are information services, individual counseling services, group guidance services and group counseling services.